The Leadership experience in Asia - Lim, Ghee Soon; Daft, Richard L. (Singapore : Thomson Learning Asia, 2004)
This book is written to bring advance concept and practices of the leadership experience, most of which originated in the west, to within the easy reach of university students and managers operating or being groomed to operate effectively in Asia.
Part One. Introduction to leadership -- Part Two. Research perspective on leadership -- Part Three. The personal side of leadership -- Part Four. The leader as relationship builder -- Part Five. The leader as a social architect.
Includes bibliographical references.
Keywords: LEADERSHIP